Preliminary Work on Speech Unit Selection Using Syntax Phonology Interface - Tiun, Sabrina; Kong, Tang Enya (2008)
This paper proposes an approach which uses a syntax-phonology interface to select the most appropriate speech units for a target sentence. The selection of the speech units is done by constructing the syntax-phonology tree structure of the target sentence. The construction of the syntax-phonology tree is adapted from the example-based parsing of UTMK machine translation.